Manganese-based positive electrode material coated with solid electrolyte as well as preparation method and application of manganese-based positive electrode material
Through a combination of microwave method and sol-gel method, the spinel lithium manganate material is linked with carbon network and coated with solid electrolyte, which solves the problem of low conductivity and manganese dissolution of the material, and significantly improves its electrochemical performance and stability.
Patent Information
- Application Number
- CN202411349546.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-21
AI Technical Summary
In practical applications, spinel lithium manganate materials have poor circulation performance due to problems such as Mn3+ disproportionation reaction and manganese dissolution, and the inherent low conductivity limits the rate performance.
The carbon network link of the lithium spinel manganate granules is used by microwave method, and solid electrolytes are used to cover the surface of lithium manganate particles on the surface of lithium manganate particles to form a lithium -lithium -lithium spinel manganate material.
It significantly improves the conductivity and ion transmission rate of lithium manganate, enhances the stability and electrochemical properties of materials, and improves the cycle stability and magnification performance of lithium batteries.
Smart Images

Figure CN119340359A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to battery materials, and in particular to a manganese-based positive electrode material coated with a solid electrolyte, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries, as the core driving force for the development of consumer electronics, energy storage systems and other key application areas, have made significant progress in energy and power density, cycle life, rate performance and battery design in recent years, bringing a new perspective to the green energy market. With the rapid progress of portable electronic products, electric vehicles and smart grid systems, the performance and cost requirements of lithium batteries are becoming increasingly stringent.
[0003] Spinel manganese-based transition metal oxide cathode materials, with their low cost and good safety, as well as the wide market supply of manganese, have dominated the small power tools and low-cost electric two-wheeled vehicle markets. With the continuous expansion of the modern energy market, this low-cost manganese-based cathode material is expected to open up a wider range of applications and occupy more market share.
[0004] However, in practical applications, spinel lithium manganese oxide materials have a 3+ The disproportionation reaction and dissolution of manganese in LiMn2O4 lead to unsatisfactory cycling performance. In addition, its inherent low conductivity (10 -6 S cm -1 ) limits the electron transfer rate of the battery under high rate conditions, affecting its rate performance. Irreversible structural damage in lithium manganese oxide and poorly conductive electrode particles are the root causes of these problems. Therefore, exploring effective modification strategies to improve the electrochemical performance of LiMn2O4 has become the focus of current research.
[0005] At present, the main modification strategy for the manganese dissolution problem is to construct a surface coating layer, using metal oxides, fluorides, polymers, etc. as coating materials to inhibit the acid-catalyzed disproportionation reaction in the electrolyte to a certain extent and protect the surface structure of the material. However, the incompleteness and heterogeneity of the coating layer cannot significantly prevent capacity decay, and the high impedance surface may hinder the ion and electron transport channels on the LiMn2O4 surface, thereby affecting its electrochemical performance. For the problem of low conductivity of electrode materials, the methods of coating carbon (such as graphene, organic carbon) and adjusting the proportion of conductive agents are often used to enhance the conductivity between electrode particles, but the effect of isolated conductive carbon is not ideal.
[0006] Therefore, it is extremely important to develop a new preparation technology to prepare manganese-based positive electrode materials coated with solid electrolytes with better performance. This will help overcome the limitations of existing materials, further improve the performance of lithium batteries, and thus promote the sustainable development of the green energy market. Summary of the invention
[0007] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for preparing a manganese-based positive electrode material coated with a solid electrolyte, wherein the positive electrode material prepared by the method has higher electrical conductivity and higher stability.
[0008] According to one aspect of the present invention, a method for preparing a manganese-based positive electrode material coated with a solid electrolyte is provided, comprising the following steps:
[0009] S1, mixing a spherical spinel lithium manganate precursor with a graphene solution, and reacting them at 100-150° C. under microwave assistance to obtain carbon-coated spinel lithium manganate;
[0010] S2, adding a soluble lithium source I, a titanium source, an aluminum source and a phosphorus source to a mixed solution containing citric acid, ethylene glycol and water to obtain a mixed solution, adding the carbon-coated spinel lithium manganese oxide to the mixed solution, and reacting under heating conditions to form a gel mixture;
[0011] S3, aging and drying the gel mixture, and then calcining to obtain the manganese-based positive electrode material coated with the solid electrolyte;
[0012] Wherein, in step S2, the molar ratio of the total molar sum of the metal elements in the lithium source I, the titanium source and the aluminum source to the diethanol is 1 to 2:1.
[0013] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved: the scheme of the present invention uses a microwave method to connect the spinel lithium manganese oxide particles to a carbon network, thereby effectively improving the conductivity of lithium manganese oxide; at the same time, a sol-gel method is used to coat the surface of the carbon-coated lithium manganese oxide particles with high conductivity with a solid electrolyte, which reduces manganese dissolution while improving its ion transmission rate, so that the prepared positive electrode material has good stability; the positive electrode material of a similar structure prepared by the traditional method has a poor coating effect, resulting in low conductivity of the internal particles themselves and uneven external coating layers, which in turn leads to poor electrochemical performance of the material. The preparation method of the scheme of the present invention uses a microwave method combined with a sol-gel method to coat lithium manganese oxide, which can specifically solve the problems of low conductivity and manganese dissolution in traditional spinel lithium manganese oxide materials.
[0014] The microwave method can quickly and uniformly coat and disperse carbon materials in a short time to form spherical particles with a conductive carbon network inside; at the same time, the sol-gel forms a uniform and dense ion conductor layer on the surface of the particles, increasing the diffusion rate of lithium ions and reducing the contact between the internal structure and the electrolyte. This microwave-assisted solid electrolyte coating method plays an important role in improving the structure of lithium manganese oxide. The prepared spinel lithium manganese oxide has high conductivity and lithium ion diffusion coefficient, and has better cycle stability.
[0015] In some embodiments of the present invention, the preparation method further comprises the step of preparing a spherical spinel lithium manganate precursor by wet ball milling.
[0016] In some embodiments of the present invention, the preparation step of the spherical spinel lithium manganate precursor includes: wet ball milling and mixing the raw materials, drying and grinding, and then calcining, wherein at least one of anhydrous ethanol, isopropanol or acetone is used as a dispersant during the wet ball milling process. Using anhydrous organic matter such as anhydrous ethanol as a dispersant is more conducive to ball milling, and at the same time, the drying effect can be more uniform.
[0017] In some embodiments of the present invention, a dispersant such as isopropanol or acetone is also added during the wet ball milling process.
[0018] In some embodiments of the present invention, the spherical spinel lithium manganate precursor is doped or undoped with other elements.
[0019] In some embodiments of the present invention, when the spherical spinel lithium manganate precursor is doped with other elements, the preparation raw materials include a lithium source II, a manganese source and a doping source.
[0020] In some embodiments of the present invention, the doping source includes at least one of Mg, Al and Nb sources.
[0021] In some embodiments of the present invention, the Mg source is selected from at least one of magnesium nitrate, magnesium hydroxide, magnesium oxide, and magnesium acetate.
[0022] In some embodiments of the present invention, the Al source is selected from at least one of aluminum hydroxide and aluminum oxide.
[0023] In some embodiments of the present invention, the Nb source is at least one of lithium niobate, niobium hydroxide, ammonium niobium oxalate, niobium nitrate or niobium pentoxide.
[0024] In some embodiments of the present invention, the lithium source II is at least one of lithium carbonate, lithium nitrate, lithium formate, lithium hydroxide, and lithium oxide.
[0025] In some embodiments of the present invention, the manganese source is at least one of manganese dioxide, manganese tetraoxide, and manganese trioxide.
[0026] In some embodiments of the present invention, the calcination conditions in the preparation process of the spherical spinel lithium manganate precursor include at least one of the following conditions: 1) the temperature is 500-700° C.; 2) the time is 4-8 hours.
[0027] In some embodiments of the present invention, the solvent in the graphene solution is a reducing solvent such as ethylene glycol, methanol, or acetone.
[0028] In some embodiments of the present invention, the mass of the graphene is 0.1-0.3% of the mass of the lithium manganate, such as 0.2%.
[0029] In some embodiments of the present invention, the reaction conditions in step S1 further include at least one of the following conditions: 1) the reaction time is 20 to 40 minutes; 2) the upper limit of the pressure is 20 MPa.
[0030] In some embodiments of the present invention, in step S2, the lithium source I is at least one of lithium carbonate, lithium nitrate, lithium formate, lithium hydroxide, and lithium oxide.
[0031] In some embodiments of the present invention, in step S2, the titanium source is tetrabutyl titanate.
[0032] In some embodiments of the present invention, the aluminum source is at least one of aluminum nitrate and aluminum acetate.
[0033] In some embodiments of the present invention, the phosphorus source is at least one of diammonium phosphate, phosphoric acid, and diammonium hydrogen phosphate.
[0034] In some embodiments of the present invention, the molar ratio of citric acid to ethylene glycol in the mixed solution is 1: 1 to 2. When the content of ethylene glycol increases, the viscosity of the colloid will also increase.
[0035] In some embodiments of the present invention, the heating temperature in step S2 is 70-90° C., and the reaction time is 6-10 hours, such as the heating temperature is 80° C., and the reaction time is 8 hours.
[0036] In some embodiments of the present invention, the coating amount of the solid electrolyte in the manganese-based positive electrode material coated with the solid electrolyte is 0.5-3% of the mass of the lithium manganese oxide.
[0037] In some embodiments of the present invention, the solid electrolyte is Li 1+x Al x Ti 2-x(PO4)3, where x is in the range of 0≤x≤1. For example, x is 0.4, 0.5 or 0.6.
[0038] In some embodiments of the present invention, the aging and drying conditions include at least one of the following conditions: 1) the temperature is 140-160° C.; 2) the time is 3-6 hours, such as the temperature is 150° C.; the time is 4 hours.
[0039] In some embodiments of the present invention, the calcination conditions in step S3 include at least one of the following conditions: 1) the temperature is 400 to 600° C.; 2) the time is 1 to 4 hours.
[0040] According to another aspect of the present invention, a manganese-based positive electrode material coated with a solid electrolyte prepared by the above method is provided.
[0041] According to another aspect of the present invention, a method for preparing a manganese-based positive electrode material coated with a solid electrolyte and its application in preparing a battery are proposed.
[0042] The application of a preferred embodiment of the present invention has at least the following beneficial effects: the solution of the present invention has good electrochemical performance and has good application prospects in the battery field.
[0043] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0045] Figure 1 It is a comparison chart of the 0.1C first charge and discharge curves of button-type batteries assembled from the positive electrode materials prepared in Example 1 of the present invention and Comparative Examples 1 to 4.
[0046] Figure 2 The figure is a comparison chart of the cycle life curves of button-type batteries assembled with the positive electrode materials prepared in Example 1 of the present invention and Comparative Examples 1 to 4.
[0047] Figure 3 Scanning electron microscope images of the electrode materials prepared in Example 1 and Comparative Examples 5-6 of the present invention.
[0048] Figure 4 This is a graph showing the electrochemical cycle performance test results of button-type batteries assembled from the positive electrode materials prepared in Example 1, Example 2, Example 4 and Comparative Example 7 of the present invention.
[0049] Figure 5The rate performance curves of button-type batteries assembled from the positive electrode materials prepared in Example 1, Example 3 and Comparative Example 8 of the present invention. DETAILED DESCRIPTION
[0050] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.
[0051] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0052] A method for preparing a manganese-based positive electrode material coated with a solid electrolyte, the specific process is:
[0053] 1) Mix the lithium source, manganese source and three doping sources (Mg, Al, Nb) according to the stoichiometric ratio, wet ball mill and mix them with alcohol as the medium, transfer the uniformly mixed raw materials to a muffle furnace for initial calcination after drying and grinding, and obtain a spherical spinel lithium manganate powder precursor; wherein the manganese source is at least one of manganese dioxide, manganese tetraoxide and manganese trioxide; the lithium source is at least one of lithium carbonate, lithium nitrate, lithium formate, lithium hydroxide and lithium oxide; the magnesium source is at least one of magnesium nitrate, magnesium hydroxide, magnesium oxide and magnesium acetate; the aluminum source is at least one of aluminum hydroxide and aluminum oxide; the niobium source is lithium niobate, niobium hydroxide, ammonium niobium oxalate, niobium nitrate or niobium pentoxide. The initial calcination temperature is 500℃~700℃, and the calcination time is 4~8h.
[0054] 2) placing the obtained spinel lithium manganate powder precursor into a graphene solution with ethylene glycol as solvent, placing it in a sealed microwave reactor for microwave synthesis reaction at a certain temperature and time, stirring is turned on throughout the process, and after the reaction is completed, the obtained liquid-solid mixture is repeatedly filtered, washed and dried to obtain carbon-coated lithium manganate spherical particles; wherein the amount of the graphene is 2wt‰ of the mass of the lithium manganate, the temperature of the microwave reaction is 100-150°C, the reaction time is 20min-40min, and the upper limit of the pressure is 20MPa.
[0055] 3) Dissolve citric acid and ethylene glycol in deionized water at a molar ratio of 1:1. 1.4 Al 0.4 Ti 1.6 A soluble lithium source, titanium source, aluminum source and phosphorus source are added in a molar ratio of (PO4)3, and a mixed solution is obtained after dissolution; wherein the added lithium source is selected from lithium carbonate, lithium nitrate, lithium formate, lithium hydroxide, and lithium oxide; the titanium source is tetrabutyl carbonate; the aluminum source is selected from aluminum nitrate and aluminum acetate; the phosphorus source is selected from ammonium dihydrogen phosphate, phosphoric acid, and diammonium hydrogen phosphate. The added metal ions (Li + +Al 3+ +Ti 4+ ) molar ratio of the total molar amount to ethylene glycol is 1 to 4; Li 1.4 Al 0.4 Ti 1.6 The coating amount of the (PO4)3 solid electrolyte is 0.5 to 3 wt% of the mass of lithium manganese oxide.
[0056] 4) The mixed solution was stirred and heated to 80° C. in a constant temperature water bath, and the carbon-coated spinel lithium manganate powder prepared in S3 was added, and the mixture was stirred for 8 h to form a gel mixture.
[0057] 5) The gel mixture was transferred to an oven and aged and dried at 150°C for 4 h to obtain a black fluffy powder, which was ground and calcined to obtain Li 1.4 Al 0.4 Ti 1.6 Carbon-coated spinel lithium manganese oxide material coated with (PO4)3 solid electrolyte. The coating calcination temperature is 400-600°C for 1-4h.
[0058] Example 1
[0059] This example prepares a microwave-assisted solid electrolyte-coated manganese-based positive electrode material, and the specific process is as follows:
[0060] 0.016 mol of Li2CO3 and 0.0194 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2, 0.002 mol of Al(OH)3 and 0.002 mol of Nb2O5 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain a spinel lithium manganese oxide powder precursor, marked as LMO.
[0061] The obtained spinel lithium manganese oxide powder precursor is placed in a 2wt‰ graphene solution with ethylene glycol as solvent; a microwave synthesis reaction is carried out under the reaction conditions of 120°C×20min (the upper limit of the pressure is set to 20MPa), and stirring is turned on throughout the process; after the reaction is completed, the obtained liquid-solid mixture is repeatedly filtered, washed and dried to obtain carbon-coated lithium manganese oxide spherical particles, marked as LMO / C.
[0062] Citric acid and ethylene glycol were dissolved in deionized water at a molar ratio of 1:1. After complete dissolution, Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 were added in proportion according to a coating amount of 2wt%. Li 1.4 Al 0.4 Ti 1.6 (PO4)3 mixed solution, in which the added metal ions (Li + +Al 3+ +Ti 4+ ) with a molar ratio of 1:1 to ethylene glycol; under the condition of constant temperature water bath heating, the mixed solution was stirred and heated to 80°C, the prepared LMO / C powder was added, and the stirring was continued for 8 hours to form a gel mixture; the gel mixture was transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, and the black fluffy powder was ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 Carbon-coated spinel lithium manganese oxide material coated with (PO4)3 solid electrolyte, labeled as LMO / C@LATP.
[0063] Example 2
[0064] The present invention prepares a microwave-assisted solid electrolyte coated manganese-based positive electrode material, which is different from Example 1 in that the reaction temperature during the microwave process is 150°C. The specific process is:
[0065] 0.016 mol of Li2CO3 and 0.0194 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2, 0.002 mol of Al(OH)3 and 0.002 mol of Nb2O5 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain spinel lithium manganate powder.
[0066] The obtained spinel lithium manganate powder precursor is placed in a 2wt‰ graphene solution with ethylene glycol as solvent; a microwave synthesis reaction is carried out under the reaction conditions of 150°C×20min (the upper limit of the pressure is set to 20MPa), and stirring is turned on throughout the process; after the reaction is completed, the obtained liquid-solid mixture is repeatedly filtered, washed and dried to obtain carbon-coated lithium manganate spherical particles.
[0067] Citric acid and ethylene glycol were dissolved in deionized water at a molar ratio of 1:1. After complete dissolution, Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 were added in proportion according to a coating amount of 2wt%. Li 1.4 Al 0.4 Ti 1.6 (PO4)3 mixed solution, in which the added metal ions (Li + +Al 3+ +Ti 4+ ) with a molar ratio of 1:1 to ethylene glycol; under the condition of constant temperature water bath heating, the mixed solution was stirred and heated to 80°C, the prepared LMO / C powder was added, and the stirring was continued for 8 hours to form a gel mixture; the gel mixture was transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, and the black fluffy powder was ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 Carbon-coated spinel lithium manganese oxide material coated with (PO4)3 solid electrolyte.
[0068] Example 3
[0069] The present invention prepares a microwave-assisted solid electrolyte coated manganese-based positive electrode material, which is different from Example 1 in that: the added metal ions (Li + +Al 3+ +Ti 4+ ) The molar ratio of the total mole of ethylene glycol is 1:2. The specific process is:
[0070] 0.016 mol of Li2CO3 and 0.0194 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2, 0.002 mol of Al(OH)3 and 0.002 mol of Nb2O5 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain a spinel lithium manganese oxide powder precursor.
[0071] The obtained spinel lithium manganate powder precursor is placed in a 2wt‰ graphene solution with ethylene glycol as solvent; a microwave synthesis reaction is carried out under the reaction conditions of 120°C×20min (the upper limit of the pressure is set to 20MPa), and stirring is turned on throughout the process; after the reaction is completed, the obtained liquid-solid mixture is repeatedly filtered, washed and dried to obtain carbon-coated lithium manganate spherical particles.
[0072] Citric acid and ethylene glycol were dissolved in deionized water at a molar ratio of 1:1. After complete dissolution, Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 were added in proportion according to a coating amount of 2wt%. Li 1.4 Al 0.4 Ti 1.6 (PO4)3 mixed solution, in which the added metal ions (Li + +Al 3+ +Ti 4+ ) the molar ratio of the total mole of ethylene glycol is 1:2; under the condition of constant temperature water bath heating, the mixed solution is stirred and heated to 80°C, the prepared carbon-coated powder is added, and the stirring is continued for 8 hours to form a gel mixture; the gel mixture is transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, the black fluffy powder is ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 Carbon-coated spinel lithium manganese oxide material coated with (PO4)3 solid electrolyte.
[0073] Example 4
[0074] This comparative example prepares a manganese-based positive electrode material, which differs from Example 1 in that the temperature during microwave carbon coating is 100°C. The specific process is:
[0075] 0.016 mol of Li2CO3 and 0.0194 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2, 0.002 mol of Al(OH)3 and 0.002 mol of Nb2O5 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain spinel lithium manganate powder.
[0076] The obtained spinel lithium manganate powder precursor is placed in a 2wt‰ graphene solution with ethylene glycol as solvent; a microwave synthesis reaction is carried out under the reaction conditions of 100°C×20min, and stirring is turned on throughout the process; after the reaction is completed, the obtained liquid-solid mixture is repeatedly filtered, washed and dried to obtain carbon-coated lithium manganate spherical particles.
[0077] Citric acid and ethylene glycol were dissolved in deionized water at a molar ratio of 1:1. After complete dissolution, Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 were added in proportion according to a coating amount of 2wt%. Li 1.4 Al 0.4 Ti 1.6 (PO4)3 mixed solution, in which the added metal ions (Li + +Al 3+ +Ti 4+ ) with a molar ratio of 1:1 to ethylene glycol; under the condition of constant temperature water bath heating, the mixed solution was stirred and heated to 80°C, the prepared LMO / C powder was added, and the stirring was continued for 8 hours to form a gel mixture; the gel mixture was transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, and the black fluffy powder was ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 Carbon-coated spinel lithium manganese oxide material coated with (PO4)3 solid electrolyte.
[0078] Comparative Example 1
[0079] This comparative example prepares a manganese-based positive electrode material, which differs from Example 1 in that no subsequent carbon coating and solid electrolyte coating process is performed. The specific process is:
[0080] 0.016 mol of Li2CO3 and 0.0194 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2, 0.002 mol of Al(OH)3 and 0.002 mol of Nb2O5 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain a spherical spinel powder sample.
[0081] Comparative Example 2
[0082] This comparative example prepares a manganese-based positive electrode material, which differs from Example 1 in that the carbon coating process is different and the solid electrolyte is carbon coated by mechanical mixing. The specific process is:
[0083] 0.016 mol of Li2CO3 and 0.0194 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2, 0.002 mol of Al(OH)3 and 0.002 mol of Nb2O5 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain a spherical spinel powder sample.
[0084] The obtained spinel lithium manganate powder precursor was placed in a 2wt‰ graphene solution with ethylene glycol as solvent and ultrasonically dispersed for 30 minutes. The liquid was transferred to a hydrothermal autoclave for hydrothermal reaction at 240°C×8h. After the reaction was completed, it was repeatedly filtered and washed, and then dried to obtain hydrothermally carbon-coated lithium manganate spherical particles.
[0085] Dissolve citric acid and ethylene glycol in deionized water at a molar ratio of 1:1. 1.4 Al 0.4 Ti 1.6 Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 were added to (PO4)3 in a stoichiometric ratio, and Li 1.4 Al 0.4 Ti 1.6 (PO4)3 mixed solution, in which the added metal ions (Li + +Al 3+ +Ti 4 +) with a molar ratio of 1:1 to ethylene glycol; under the condition of constant temperature water bath heating, the mixed solution was stirred and heated to 80°C, and the stirring was continued for 8 hours to form a gel mixture; the gel mixture was transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, and the black fluffy powder was ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte powder; Li 1.4 Al 0.4 Ti 1.6 The (PO4)3 solid electrolyte powder was mixed with the above-mentioned hydrothermally carbon-coated lithium manganese oxide spherical powder at a coating ratio of 2 wt%, ball-milled for 6 h with isopropanol as solvent, dried and ground, and then calcined in a muffle furnace at 500 ° C × 4 h. 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte coated spinel lithium manganese oxide sample;
[0086] Comparative Example 3
[0087] This comparative example prepares a manganese-based positive electrode material, which differs from Example 1 in that the carbon coating process is different. The specific process is:
[0088] 0.016 mol of Li2CO3 and 0.0194 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2, 0.002 mol of Al(OH)3 and 0.002 mol of Nb2O5 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain a spherical spinel powder sample.
[0089] The obtained spinel lithium manganate powder precursor was placed in a 2‰ graphene solution with ethylene glycol as solvent and ultrasonically dispersed for 30 minutes. The liquid was transferred to a hydrothermal autoclave for hydrothermal reaction at 240°C×8h. After the reaction was completed, it was repeatedly filtered and washed, and then dried to obtain hydrothermally carbon-coated lithium manganate spherical particles.
[0090] Citric acid and ethylene glycol were dissolved in deionized water at a molar ratio of 1:1. After complete dissolution, Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 were added in proportion according to a coating amount of 2wt%. Li 1.4 Al 0.4 Ti 1.6(PO4)3 mixed solution, in which the added metal ions (Li + +Al 3+ +Ti 4+ ) with a molar ratio of 1:1 to ethylene glycol; under the condition of constant temperature water bath heating, the mixed solution was stirred and heated to 80°C, and the lithium manganate powder coated with carbon by the hydrothermal method was added, and the stirring was continued for 8 hours to form a gel mixture; the gel mixture was transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, and the black fluffy powder was ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte coated spinel lithium manganese oxide sample.
[0091] Comparative Example 4
[0092] This comparative example prepares a manganese-based positive electrode material, which differs from Example 1 in that a ball milling method is used to coat the solid electrolyte. The specific process is:
[0093] 0.016 mol of Li2CO3 and 0.0194 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2, 0.002 mol of Al(OH)3 and 0.002 mol of Nb2O5 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain a spherical spinel powder precursor.
[0094] The obtained spinel lithium manganate powder precursor is placed in a 2wt‰ graphene solution with ethylene glycol as solvent, placed in a sealed microwave reactor, and subjected to microwave synthesis reaction under the reaction conditions of 120°C×20min, with stirring turned on throughout the process; after the reaction is completed, the obtained liquid-solid mixture is repeatedly filtered and washed, and after drying, a microwave-coated carbon-type lithium manganate spherical sample is obtained.
[0095] Dissolve citric acid and ethylene glycol in deionized water at a molar ratio of 1:1, and add Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 in proportion after they are completely dissolved. 1.4 Al 0.4 Ti 1.6 (PO4)3 mixed solution, in which the added metal ions (Li + +Al 3+ +Ti 4+) with a molar ratio of 1:1 to ethylene glycol; under the condition of constant temperature water bath heating, the mixed solution was stirred and heated to 80°C, and the stirring was continued for 8 hours to form a gel mixture; the gel mixture was transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, and the black fluffy powder was ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte powder; Li 1.4 Al 0.4 Ti 1.6 The (PO4)3 solid electrolyte powder was mixed with the above microwave carbon-coated lithium manganese oxide spherical powder at a coating ratio of 2 wt%, ball-milled for 6 h with isopropanol as solvent, dried and ground, and then calcined in a muffle furnace at 500 ° C × 4 h. 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte coated spinel lithium manganese oxide sample.
[0096] Comparative Example 5
[0097] This embodiment prepares a manganese-based positive electrode material, which is different from the embodiment 1 in that the initial spinel lithium manganese oxide is not doped with other elements. The specific process is:
[0098] 0.16 mol of Li2CO3 and 0.02 mol of Mn3O4 raw materials were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain an undoped spinel lithium manganese oxide powder sample.
[0099] The obtained spinel lithium manganate powder precursor is placed in a 2wt‰ graphene solution with ethylene glycol as solvent; a microwave synthesis reaction is carried out under the reaction conditions of 120°C×20min (the upper limit of the pressure is set to 20MPa), and stirring is turned on throughout the process; after the reaction is completed, the obtained liquid-solid mixture is repeatedly filtered, washed and dried to obtain carbon-coated lithium manganate spherical particles.
[0100] Citric acid and ethylene glycol were dissolved in deionized water at a molar ratio of 1:1. After complete dissolution, Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 were added in proportion according to a coating amount of 2wt%. Li 1.4 Al 0.4 Ti 1.6 (PO4)3 mixed solution, in which the added metal ions (Li + +Al3+ +Ti 4+ ) with a molar ratio of 1:1 to ethylene glycol; under the condition of constant temperature water bath heating, the mixed solution was stirred and heated to 80°C, the prepared LMO / C powder was added, and the stirring was continued for 8 hours to form a gel mixture; the gel mixture was transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, and the black fluffy powder was ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 Carbon-coated spinel lithium manganese oxide material coated with (PO4)3 solid electrolyte.
[0101] Comparative Example 6
[0102] This embodiment prepares a manganese-based positive electrode material, which is different from the embodiment 1 in that it is not doped with Nb. The specific process is:
[0103] 0.016 mol of Li2CO3 and 0.0196 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2 and 0.002 mol of Al(OH)3 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain a spherical spinel powder sample.
[0104] The obtained spinel lithium manganate powder precursor is placed in a 2wt‰ graphene solution with ethylene glycol as solvent; a microwave synthesis reaction is carried out under the reaction conditions of 100°C×20min, and stirring is turned on throughout the process; after the reaction is completed, the obtained liquid-solid mixture is repeatedly filtered, washed and dried to obtain carbon-coated lithium manganate spherical particles.
[0105] Citric acid and ethylene glycol were dissolved in deionized water at a molar ratio of 1:1. After complete dissolution, Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 were added in proportion according to a coating amount of 2wt%. Li 1.4 Al 0.4 Ti 1.6 (PO4)3 mixed solution, in which the added metal ions (Li + +Al 3+ +Ti 4+) with a molar ratio of 1:1 to ethylene glycol; under the condition of constant temperature water bath heating, the mixed solution was stirred and heated to 80°C, the prepared LMO / C powder was added, and the stirring was continued for 8 hours to form a gel mixture; the gel mixture was transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, and the black fluffy powder was ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 Carbon-coated spinel lithium manganese oxide material coated with (PO4)3 solid electrolyte.
[0106] Comparative Example 7
[0107] This comparative example prepares a manganese-based positive electrode material, which differs from Example 1 in that the temperature during microwave carbon coating is 200°C. The specific process is:
[0108] 0.016 mol of Li2CO3 and 0.0194 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2, 0.002 mol of Al(OH)3 and 0.002 mol of Nb2O5 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain spinel lithium manganate powder.
[0109] The obtained spinel lithium manganate powder precursor is placed in a 2wt‰ graphene solution with ethylene glycol as solvent; a microwave synthesis reaction is carried out under the reaction conditions of 200°C×20min, and stirring is turned on throughout the process; after the reaction is completed, the obtained liquid-solid mixture is repeatedly filtered, washed and dried to obtain carbon-coated lithium manganate spherical particles.
[0110] Citric acid and ethylene glycol were dissolved in deionized water at a molar ratio of 1:1. After complete dissolution, Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 were added in proportion according to a coating amount of 2wt%. Li 1.4 Al 0.4 Ti 1.6 (PO4)3 mixed solution, in which the added metal ions (Li + +Al 3+ +Ti 4+) with a molar ratio of 1:1 to ethylene glycol; under the condition of constant temperature water bath heating, the mixed solution was stirred and heated to 80°C, the prepared LMO / C powder was added, and the stirring was continued for 8 hours to form a gel mixture; the gel mixture was transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, and the black fluffy powder was ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 Carbon-coated spinel lithium manganese oxide material coated with (PO4)3 solid electrolyte;
[0111] Comparative Example 8
[0112] This comparative example prepares a manganese-based positive electrode material, which differs from Example 1 in that: the added metal ions (Li + +Al 3+ +Ti 4+ ) The molar ratio of the total mole of ethylene glycol is 1:3. The specific process is:
[0113] 0.016 mol of Li2CO3 and 0.0194 mol of Mn3O4 raw materials, 0.002 mol of Mg(OH)2, 0.002 mol of Al(OH)3 and 0.002 mol of Nb2O5 were placed in a ball mill and wet-milled with anhydrous ethanol as the medium (350 r / min×8 h). After drying at 120°C for 12 h, the powder was ground and transferred to a muffle furnace for initial calcination at 650×12 h to obtain a spinel lithium manganese oxide powder precursor.
[0114] The obtained spinel lithium manganate powder precursor is placed in a 2wt‰ graphene solution with ethylene glycol as a solvent; a microwave synthesis reaction is carried out under the reaction conditions of 120°C×20min, and stirring is turned on throughout the process; after the reaction is completed, the obtained liquid-solid mixture is repeatedly filtered, washed and dried to obtain carbon-coated lithium manganate spherical particles;
[0115] Citric acid and ethylene glycol were dissolved in deionized water at a molar ratio of 1:1. After complete dissolution, Li3NO3, Al(NO3)3·9H2O, Ti(OCH2CH2CH2CH3)4 and NH4H2PO4 were added in proportion according to a coating amount of 2wt%. Li 1.4 Al 0.4 Ti 1.6 (PO4)3 mixed solution, in which the added metal ions (Li + +Al 3+ +Ti 4+) the molar ratio of the total mole of ethylene glycol is 1:3; under the condition of constant temperature water bath heating, the mixed solution is stirred and heated to 80°C, the prepared carbon-coated powder is added, and the stirring is continued for 8 hours to form a gel mixture; the gel mixture is transferred to an oven and aged and dried at 150°C for 4 hours to obtain a black fluffy powder, the black fluffy powder is ground and calcined in a muffle furnace at 500°C for 2 hours to obtain Li 1.4 Al 0.4 Ti 1.6 Carbon-coated spinel lithium manganese oxide material coated with (PO4)3 solid electrolyte.
[0116] Test Case
[0117] The manganese-based positive electrode material sample obtained by the above operation was crushed, ground, and sieved as the positive electrode active material, and then added to N-methylpyrrolidone solvent with acetylene black and PVDF in a mass ratio of 8:1:1 and mixed evenly; the ground uniform slurry was coated on aluminum foil and dried at 120°C for 12 hours, and then cut into pieces to obtain positive electrode sheets. The lithium sheet was used as the negative electrode, the PE film was used as the separator, and LiPF6 was used as the electrolyte to assemble a 2016-type button battery in a glove box.
[0118] The electrochemical performance of button-type half-cells of the above embodiments and comparative examples was tested under the test conditions of a voltage range of 3.5V to 4.3V (0.1C = 148mAh / g) and a test temperature of 25°C.
[0119] The first charge and discharge curves of the button cells assembled from the positive electrode materials obtained in Example 1 and Comparative Examples 1 to 4 are as follows: Figure 1 As shown, it is clearly observed that the first discharge specific capacity of Example 1 and other comparative examples is significantly increased compared to the sample without carbon coating and solid electrolyte coating (Comparative Example 1). This is because the addition of carbon can improve the conductivity of the material, increase its electron transfer rate, and increase the initial discharge specific capacity; however, the addition of the LATP solid electrolyte layer will slightly reduce its initial discharge specific capacity. This is because the heterogeneous layer structure as an inactive layer does not participate in the oxidation reaction; it can be seen from Example 1 and Comparative Examples 2 to 4 that the microwave carbon coating method is significantly better than the hydrothermal method and the process of the solid electrolyte coating layer will also affect its initial discharge specific capacity. Figure 1 It can be seen that the use of mechanical mixing is not conducive to the initial efficiency. Due to the difference in coating effect, the dissolution of manganese is aggravated, and the discharge specific capacity decreases compared to the sol-gel method.
[0120] The cycle performance test results of the button-type batteries assembled with the positive electrode materials prepared in Example 1 and Comparative Examples 1 to 4 at a current density of 1C are as follows: Figure 2As shown in the figure, it can be seen that Example 1 exhibits excellent cycle stability, which drops from the initial 134.3mAh / g to 111.4mAh / g after 200 cycles, and the retention rate reaches 82.9%; this is mainly due to the microwave method to carbonize the interior of the lithium manganese oxide particles to improve their conductivity, and at the same time, the surface coating of the solid electrolyte layer can effectively protect the structural stability of the material in a long cycle and provide a channel for the transmission of lithium ions. This microwave-assisted solid electrolyte coating method effectively improves the material's cycle performance and structural stability.
[0121] Figure 3 The scanning electron microscope images of the samples of Example 1 (a), Comparative Example 5 (b) and Comparative Example 6 (c) clearly show the difference in the surface morphology of the spinel lithium manganese oxide samples. The particles of the samples doped with Mg / Al / Nb are spherical, while those that are not doped or doped with only two elements show irregular octahedral morphology. For spinel lithium manganese oxide electrode materials, the surface structure is closely related to the electrochemical performance. The spherical particle morphology can effectively improve the energy density of the material. This is indeed the case after testing.
[0122] Figure 4 The electrochemical cycle performance of the samples of Example 1, Example 2, Example 4 and Comparative Example 7 is shown. The results show that the temperature of the microwave carbon coating has a great influence on the electrochemical performance of the samples. In Comparative Example 7, since the microwave temperature reaches 200°C, the lithium manganese oxide sample may be reduced, and the initial discharge specific capacity is only 86.4 mAh / g, which further affects its subsequent electrochemical performance.
[0123] Figure 5 The rate performance curves of the samples in Example 1, Example 3 and Comparative Example 8 show that the ratio of ethylene glycol to metal ions needs to be controlled during the sol-gel coating of the LATP solid electrolyte layer. When the ethylene glycol ratio is high, the sol-gel coating effect is poor, resulting in poor rate performance under high current charge and discharge conditions. This is because if the ethylene glycol ratio is too high, the solution becomes viscous, which is not conducive to the complexation of the colloid, resulting in poor coating effect.
[0124] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a manganese-based positive electrode material coated with a solid electrolyte, characterized in that: The steps include: S1, mixing a spherical spinel lithium manganate precursor with a graphene solution, and reacting them at 100-150° C. under microwave assistance to obtain carbon-coated spinel lithium manganate; S2, adding a soluble lithium source I, a titanium source, an aluminum source and a phosphorus source to a mixed solution containing citric acid, ethylene glycol and water to obtain a mixed solution, adding the carbon-coated spinel lithium manganese oxide to the mixed solution, and reacting under heating conditions to form a gel mixture; S3, aging and drying the gel mixture, and then calcining to obtain the manganese-based positive electrode material coated with the solid electrolyte; Wherein, in step S2, the molar ratio of the total molar sum of the metal elements in the lithium source I, the titanium source and the aluminum source to the diethanol is 1 to 2:
1.
2. The method for preparing a manganese-based positive electrode material coated with a solid electrolyte according to claim 1, characterized in that: The preparation steps of the spherical spinel lithium manganate precursor include: wet ball milling and mixing the raw materials, drying and grinding, and then calcining, wherein at least one of anhydrous ethanol, isopropanol or acetone is used as a dispersant during the wet ball milling process.
3. The method for preparing a manganese-based positive electrode material coated with a solid electrolyte according to claim 1, characterized in that: The spherical spinel lithium manganate precursor is doped with other elements, and the preparation raw materials include lithium source II, manganese source and doping source, and the doping source includes at least one of Mg, Al and Nb sources.
4. The method for preparing a manganese-based positive electrode material coated with a solid electrolyte according to claim 1, characterized in that: The Mg source is selected from at least one of magnesium nitrate, magnesium hydroxide, magnesium oxide, and magnesium acetate; and / or, the Al source is selected from at least one of aluminum hydroxide and aluminum oxide; and / or, the Nb source is at least one of lithium niobate, niobium hydroxide, ammonium niobium oxalate, niobium nitrate, or niobium pentoxide; and / or, the lithium source II is at least one of lithium carbonate, lithium nitrate, lithium formate, lithium hydroxide, and lithium oxide; and / or, the manganese source is at least one of manganese dioxide, manganese tetraoxide, and manganese trioxide.
5. The method for preparing a manganese-based positive electrode material coated with a solid electrolyte according to claim 1, characterized in that: The calcination conditions in the preparation process of the spherical spinel lithium manganate precursor include at least one of the following conditions: 1) the temperature is 500-700° C.; 2) the time is 4-8 hours.
6. The method for preparing a manganese-based positive electrode material coated with a solid electrolyte according to claim 1, characterized in that: The heating temperature in step S2 is 70-90° C., and the reaction time is 6-10 hours.
7. The method for preparing a manganese-based positive electrode material coated with a solid electrolyte according to claim 1, characterized in that: The coating amount of the solid electrolyte in the manganese-based positive electrode material coated with the solid electrolyte is 0.5-3% of the mass of the lithium manganate.
8. The method for preparing a manganese-based positive electrode material coated with a solid electrolyte according to claim 1, characterized in that: In step S3, at least one of the following conditions is met: 1) The solid electrolyte is Li 1+x Al x Ti 2-x (PO4)3, where the value range of x is 0≤x≤1; 2) The aging and drying conditions include at least one of the following conditions: 1) the temperature is 140 to 160° C.; 2) the time is 3 to 6 hours; 3) The calcination conditions in step S3 include at least one of the following conditions: 1) the temperature is 400-600° C.; 2) the time is 1-4 hours.
9. A manganese-based positive electrode material coated with a solid electrolyte obtained according to the preparation method according to any one of claims 1 to 8.
10. Use of the method for preparing a manganese-based positive electrode material coated with a solid electrolyte according to any one of claims 1 to 8 in preparing a battery.
Citation Information
Patent Citations
Layered structure nanometer lithium manganate-inlaid graphene-coated positive electrode material for lithium-ion battery, electrode and preparation method
CN105958055A
A lithium manganate positive electrode material with high magnification and a preparation method thereof are provide
CN109004212A
Method for microwave-assisted synthesis of reduced graphene oxide coated nickel cobalt lithium manganate positive electrode material
CN113299891A
LiAlSiPO4-coated double-donor-doped spinel lithium manganate material as well as preparation method and application thereof
CN115799477A
Cited By
Preparation method of solid electrolyte homogeneous-phase coated positive electrode material
CN121894716A
A plastic crystal phosphate coated spinel lithium manganate composite material, a preparation method and application thereof
CN122992008A